Influence of the Minho River plume on the Rias Baixas (NW of the iberian peninsula) - Sousa, M. C.
The buoyancy generated by the Minho estuarine plume can flood the Rias Baixas for long periods, reversing the normal salinity gradients. Thus, the main purpose of this work was to study the propagation of Minho estuarine plume to the Rias Baixas, establishing the wind and river discharge conditions in which this plume affects the circulation and hydrography features of these coastal systems as well as the plume characteristics under the most probable forcing conditions, through the application of the numerical model MOHID. For this purpose, several scenarios with different river discharges and wind were simulated. The numerical results revealed that the Minho estuarine plume responds rapidly to wind variations and is influenced by coastline geometry. Under Minho River discharges higher than 700m3s-1 and weak northward winds (3ms-1) the circulation patterns of the Rias de Vigo and Pontevedra are reversed. On the other hand, moderate northward winds (6ms-1) combined with Minho River discharges higher than 200m3s-1, 300m3s-1 and 700m3s-1 reverse the circulation pattern of the Rias de Vigo, Pontevedra and Arousa, respectively. Under the same conditions, the water exchange between Rias Baixas was analyzed using a particle-tracking model following the trajectories of particles released close to the Minho River mouth. Over 5days, under Minho River discharges higher than 2100m3s-1 combined with northward winds of 6ms-1, an intense water exchange between Rias was observed. However, only 20% of the particles found in Ria de Pontevedra come directly from the Minho River.